Rheological properties of mixed gels of oat ß-glucan and whey proteins - Gustaw, W.; Szwajgier, D. (Polimery, 2012)
The solutions of whey protein isolates (WPI) with the addition of various amounts (0.05—0.5 %) of ß-glucan (oat gum — OG) were subjected to gelation process by heating them up to 80 °C. The effects of pH and OG content on the rheological properties of the obtained gels were studied. The presence of oat gum in the solutions of whey protein isolates gave rise to the changes in the temperature of gelation, shear at fracture and storage modulus of the mixed gels obtained from the solutions of different pH. The gels with the most favourable properties were prepared from the solutions of whey proteins of pH 3 with the addition of 0.3 % oat gum. The mixed gels of WPI and OG can be used to enhance rheological properties of foodstuffs, especially those of acidic and neutral character.